Beritakan Firman Baik atau Tidak Baik Waktunya: Signifikansi bagi Ibadah Online - DESI NATALIA SBP; Ferdinan Samuel Manafe (Jurnal Arrabona, 2023)
ABSTRACT Preaching the Word can be done through several forms and means, not just face-to-face. Increasingly advanced technology is an opportunity and means that can be used so that everyone can preach the Word and have a wider reach. Technology that supports the preaching of the Word is through social media. The outbreak of the Covid-19 virus has resulted in services that are held face-to-face being replaced with online worship which can be a means of preaching the Word to everyone so that everyone can hear the Good News under any circumstances and anywhere. But for some people, both preachers of the Word and those who listen to the Word, online worship is less effective because there are many distractions, internally and externally. The ordinances of worship which are limited by space and time as well as the solemn rules that have become the standard of the church have changed. There are even some God's servants who are concerned about the existing limitations, as well as the lack of tools used for online worship. Also, not a few servants and servants of God try to be able to preach as creatively as possible, so that the congregation faithfully follows their worship. This article which is written descriptively through a literature study seeks to describe the significance of preaching the Word of God based on 2 Timothy 4:2 for online worship so that both preachers, congregations, and churches can use the opportunity to spread the truth of the Gospel through social media and be a blessing not only to his own congregation but also for everyone who listens to sermons online.